The Impact of the Influencer Economy on Gen Z's Impulse Buying Behavior: An Empirical Study Using the SOR Model - Jinqi Chen; Jirapong Ruanggoon (Journal of Frontier in Economic and Management Research, 2026)
To explore the mechanisms by which the influencer economy affects Generation Z's impulse buying behavior, this study, based on the SOR model, surveyed 500 Chinese Gen Z consumers who had made purchases recommended by influencers within the past three months. Descriptive statistics, reliability analysis, confirmatory factor analysis (CFA), structural equation modeling (SEM), and Bootstrap mediation tests were employed for empirical analysis. The results revealed that influencer traits, content quality, promotional activities, and monetization strategies all had significant positive effects on Gen Z's impulse buying behavior. Perceived value and pleasure played a significant mediating role between these stimuli and impulse buying behavior, demonstrating a "cognitive-affective" dual-pathway mechanism. Specifically, promotional activities stimulated price-sensitive impulses, influencer traits and content quality enhanced emotional motivation, and monetization strategies enhanced perceived value and purchase intention through contextualized placement. This study expanded the application of the SOR model in the context of digital consumption and provided practical references for content creators, brands, and platforms to promote rational consumption among Generation Z.